The relationship between organisational commitment, job satisfaction and turnover intention in the Department of rural Development and Land Reform, Limpopo Province - Ramogale, Mainetsa Adolph (University of Limpopo, 2016)
The purpose of this study is to explain the relationship between organisational commitment, job satisfaction and turnover intention of employees. A survey research design was employed to test hypotheses about the relationship between job satisfaction, organisational commitment and turnover intentions. Data was collected using three different structured questionnaires. Questionnaires comprised of the Minnesota Satisfaction Questionnaire, the Organisational Commitment Questionnaire and the Intention to Stay Questionnaire. The respondents comprised of employees from five offices of the Department of Rural Development and Land Reform in the Limpopo Province. The findings revealed a positive relationship between organisational commitment and job satisfaction. There is a negative relationship between organisational commitment and turnover intention. Tables and figures were used to present the results of the study. Turnover intention has been seen as a huge problem at different organisations or institutions and has negative influence on organisational performance and this organisation was not different given the findings. Key concepts Organisational commitment, job satisfaction, turnover intention.
Thesis (M.Com.(Human Resource Management)) -- University of Limpopo, 2016
Keywords: Organisational commitment; Job satisfaction; Turnover intentions; Job satisfaction; Employment stabilization